RECIPROCAL ACTION OF PENTRAXIN-3 AND CRP IN WOMEN WITH POLYCYSTIC OVARY SYNDROME - (:unkn) unknown (BIOLIFE SAS, 2014)
The aim of this study was to investigate the relationship between pentraxin-3 and other biochemical parameters in women with polycystic ovary syndrome (PCOS). We compared 58 women with PCOS to 34 body mass index- and age-matched normally menstruating healthy controls. Women with PCOS had significantly higher DHEA-S, free testosterone, LH and FM, but lower pentraxin-3 levels when compared to healthy controls (0.86 +/- 0.21 and 0.91 +/- 0.14 respectively, p=0.014). Levels of CRP and lipoprotein-a were higher in the PCOS group. Overweight PCOS had significantly higher insulin, HOMA-IR, FAI, free testosterone and CRP and statistically significantly lower HDL and SHBG levels when compared to controls. Pentraxin-3 levels of obese and normal weight PCOS were similar. CRP and pentraxin-3 might contribute reciprocally to metabolic events and chronic low-grade inflammation in women with PCOS.
Keywords: inflammation; pentraxin-3; polycystic ovary syndrome; lipoprotein-a; CRP; C-REACTIVE PROTEIN; SERUM AMYLOID-P; ADIPOSE-TISSUE; INSULIN-RESISTANCE; METABOLIC SYNDROME; 3 PTX3; INFLAMMATION; OBESITY; RISK; HOMOCYSTEINE